2021
DOI: 10.1186/s12877-021-02043-x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective cohort study of the risk factors for new falls and fragility fractures in self-caring elderly patients aged 80 years and over

Abstract: Background This study aimed to prospectively analyze the risk factors for new falls and fragility fractures in self-caring elderly patients and to find suitable evaluation tools for community screening and follow-up interventions. Methods: A total of 300 participants (187 male and 113 female), aged 80 or above and capable of caring for themselves, were enrolled in this study and observed for a period of 12 months. Their medical histories were collected, various indicators were measured, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 29 publications
0
14
0
2
Order By: Relevance
“…However, inconsistent result observed in the correlation between walking speed and fragility fracture. From this research, walking speed has shown to have no direct correlation with fragility fractures (16). Instead, reduced outdoor activities, reduced walking speed and increased TUG result were more likely to cause a new fall, which increase fragility fracture among elderly.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…However, inconsistent result observed in the correlation between walking speed and fragility fracture. From this research, walking speed has shown to have no direct correlation with fragility fractures (16). Instead, reduced outdoor activities, reduced walking speed and increased TUG result were more likely to cause a new fall, which increase fragility fracture among elderly.…”
Section: Discussionmentioning
confidence: 68%
“…A total of 12 studies were selected for this systematic review (Figure 1). Six studies were rated as good quality (16,18,(22)(23)(24)26) and another six rated as fair quality (17,(19)(20)(21)25,27).…”
Section: Flow Of Studies In the Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of performing ADL independently, the literature reports that high scores on the Barthel indices were negatively correlated with experiencing new falls (25). Similarly, experiencing a fall or its recurrence increases its prevalence in individuals with low BADL scores (26).…”
Section: Discussionmentioning
confidence: 99%